Proposal for the Promotion of Standardization of Precast Beams in Highway Concrete Bridges - Antoniou, Fani; Marinelli, Marina (Frontiers in Built Environment, 2020)
Precast concrete beams for bridges are among the widely used applications of off-site construction with various standardized profiles and lengths being long used in different national contexts. The purpose of this paper is to highlight the important role of standardization in construction and promote the use of prefabrication in the design and construction of highway concrete bridges in countries with low construction industrialization. In this context, this research proposes a set of 45 standard precast extended – I beams, suitable for use in the majority of the common motorway bridge configurations. The selection of the proposed set of standard beams has emerged from data of 109 bridges (2,284 beams in total) constructed along the Egnatia Motorway and two of its perpendicular axes in Greece. Specifically, a database including the dimensions of the precast beams as built (length, depth, upper flange width (UFW), lower flange width (LFW) and web width (WW)), was first created. Following careful data review, 36 different combinations of depth, UFW and LFW and 64 different lengths were detected. Τhis, as well as further data analysis, demonstrated that in the project of Egnatia Motorway no attempt was made to globally standardize the beam configurations; as a result the efficiency benefits typifying standardization were not captured. Therefore, the dataset’s variables were subject to thorough statistical analysis, including multi-linear regression and correlation analysis, with the aim to determine a set of standard beam configurations. The resulting set of 45 beams represents 15 different lengths, coupled with 3 alternative depths each, in compliance to the regulatory requirements for the bridge’s effective width. Furthermore, this paper makes specific suggestions for a more effective procurement strategy which will be incorporating award criteria in favor of the use of off-site construction as well as the development of official guidelines enforcing the use of standard design elements. The important role of suitable contracts as well as the provision of training to the main stakeholders involved, are also highlighted. This proposal can help Greece, as well as other countries with non-well-established relevant standards, launch an effective strategy aimed at harnessing standardization’s efficiency benefits in bridge construction.